LENGTH-WEIGHT RELATIONSHIP OF MARINE COMMERCIAL FISH SPECIES IN RIO DE JANEIRO STATE, BRAZIL - Tubino, Magda Fernandes de Andrade; Paiva, Melquíades Pinto (Arquivos de Ciências do Mar, 2007)
Length-weight relationship parameters of thirteen species of demersal and pelagic fishes that are of economic and ecological relevance in the commercial fisheries of Rio de Janeiro State, southeastern of Brazil, are presented. These relationships indicate a positive allometry tendency for the regression slope, b in the sampled fish community.